Descriptive analysis of 179 German reports of melanoma reported to an adverse drug reaction database as a drug‐related adverse effect, and comparison with melanoma cases contained in German cancer registries. (14th March 2022) - Sachs, Bernhardt; Dubrall, Diana; Kraywinkel, Klaus; Schulz, Maike; Schmid, Matthias; Bate, Jens; Fischer‐Barth, Wilma
Summary: Background: Malignant melanoma (MM) is one of the most aggressive forms of skin cancer. The occurrence of MM associated with drug therapy has been described in the literature. However, there is no analysis of a substantial number of validated reports of drug‐associated MM. Aim: To analyse a substantial number of validated spontaneous reports of drug‐associated MM with regard to the suspected drug and the reported characteristics, and to compare these analyses with those of MM cases occurring in the general population in Germany. Methods: Spontaneous reports of MM associated with drug therapy in Germany were identified in a large adverse drug reaction database (EudraVigilance). These results were then compared with analyses of MMs in the pooled data from a population‐based German cancer registry. Results: The 10 most frequently suspected drugs in the MM reports all target the immune system, with 7 of these being immunosuppressants. The median time to onset to MM diagnosis was 2.0 years. Patients with drug‐associated MM were 11 years (median) younger than patients with MM in the cancer registry, and this age difference was greater for female than for male patients. Conclusions: Our results emphasize the importance of regular dermatological examinations of patients being treated with immunosuppressants. Physicians should be aware that in these patients, MM might be detected at younger ages and even within 2 years after initiating therapy. Abstract : We analysed adverse drug reaction reports of drug‐associated melanoma from Germany and compared them to the cases of naturally occurring melanoma in the German population. Both the annual number of melanoma reports and the estimated crude incidence rates of naturally occurring melanoma increased in the period investigated.